Analisis Proksimat Mie Sorame: Mie Substitusi Sorgum (Sorgum bicolor L. Moench) dan Edamame (Glycine max (L.) Merill) - Indis, Nadhifah; Adhamatika, Adhima; Yani, Subaktilah; Rosyadi, A. Sirojul Anam Izza; Rakhmadina, Casilda Aulia (Politeknik Negeri Jember, 2026)
Sorghum is a gluten-free grain that has the potential to be used as an alternative substitute for wheat flour. There are two types of sorghum red sorghum and white sorghum). The sorghum we used in this study is the red sorghum (Sorghum bicolor L. Moench). Exploration of sorghum flour as the main ingredient for noodles is relatively limited if compared with corn, rice, and mocaf. This study aims to determine proximate content of SORAME noodles (Sorghum and Edamame Substitution). The method using CRD design with 5 treatments and 3 replications. The resulting data was analyzed statistically (normality, ANOVA, and LSD Fischer) using SPSS software at significance level of 0.05. Water content, ash content, and crude fiber analysis results are tended to increase with increasing sorghum flour, while the protein and carbohydrate content tended to decrease. The lowest water content (34.50%), the highest protein (5.75%) and the highest carbohydrate (60.05%) were obtained from SRM0, the highest ash (1.46%) and the highest fiber (14,15%) was obtained from the SRM4. Based on these results, the best formulation is SRM4 (sorghum and wheat flour 60:40). This formulation has high fiber and ash mineral content, but low carbohydrate and gluten.